Reformulating the Concept of Plea Bargaining in the Criminal Justice System Following the New Criminal Code and Criminal Procedure Code - Albi Ternando; Adithya Diar; Nella Octaviany Siregar; M.Havidz Aima (Greenation Research & Yayasan Global Resarch National, 2026)
This study analyzes the regulation and formulates an ideal model for implementing plea bargaining in Indonesia’s criminal justice system following the enactment of Law Number 1 of 2023 on the Criminal Code and Law Number 20 of 2025 on the Criminal Procedure Code. The study is based on the structural inconsistency between substantive criminal law, which has shifted toward a rehabilitative paradigm, and procedural criminal law, which still reflects a retributive approach. This research uses a normative juridical method with statutory and conceptual approaches. The findings show that the regulation of plea bargaining under the 2025 Criminal Procedure Code still contains significant normative inconsistencies, particularly regarding sentencing limits, procedural stages, and the legal form of decisions in summary proceedings. In addition, the expansion of legal evidence confirms that a confession cannot be the sole basis for conviction. Therefore, plea bargaining must be reformulated not only as a mechanism for judicial efficiency but also as a legal instrument that ensures due process of law, legal certainty, protection of defendants’ rights, and harmony with restorative justice and alternative sentencing policies in Indonesia.